Water, Life and Civilisation : Climate, Environment and Society in the Jordan Valley. - Mithen, Steven (International hydrology series., 2011)
Unique interdisciplinary study of relationships between climate, hydrology and human society in the Jordan Valley for researchers and advanced students.